A Franco-American Overview. Volume 5. Louisiana - Allain, Mathe, Comp.; Brasseaux, Carl A., Comp.; National Assessment and Dissemination Center for Bilingual Education, Cambridge, MA.; National Materials Development Center for French and Portuguese, Bedford, NH. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
Intended to help readers develop an appreciation of the contributions of Franco-Americans to the cultural heritage of the United States, this book, the fifth of six volumes, presents 18 chapters representing many perspectives--from the historical to the sociological--illustrating the thinking and feelings of those in the forefront of Franco-American studies. This volume focuses on Franco-Americans in Louisiana. The following readings are presented: "France and the Mississippi Valley: A Resume" (Louise Phelps Kellogg); "France and Louisiana in the Early Eighteenth Century" (Marcel Giraud); "Bienville's First Administration" (Charles Edward O'Neill); "Private Enterprise vs. Mercantilism: The Cadillac-Duclos Affair" (Carl A. Brasseaux); "The Superior Council in Colonial Louisiana" (James D. Hardy, Jr.); "The Development of Industries in Louisiana During the French Regime, 1673-1763" (Nancy M. Miller Surrey); "An Adventurous Voyage to French Colonial Louisiana: The Narrative of Mother Tranchepain, 1727" (Marion Ware); "The Establishment of a Colonist" (Antoine-Simon Le Page Du Pratz); "From African Captivity to American Slavery: The Introduction of Black Laborers to Colonial Louisiana" (Daniel H. Usner, Jr.); "The French and the Natchez Indians in Louisiana: 1700-1731" (Patricia D. Woods); "La Louisiane avant Vaudreuil" ("Louisiana before Vaudreuil," Guy Fregault) "New Orleans under French Rule" (Sarah Searight); "Les problemes d'installation des Acadiens en Louisiane au XVIIIe siecle" ("Settlement Problems of the Acadians in Louisiana in the 18th Century," Jacqueline Voorhies); "The New Orleans Revolution of 1768: A Reappraisal" (Richard Ira Matthews); "Some Eighteenth-Century French Views on Louisiana" (Pierre H. Boulle); "Louisiana as a Factor in French Diplomacy from 1762 to 1800" (Mildred Stahl Fletcher); "The World Aspects of the Louisiana Purchase (William M. Sloane); and "The Transfer" (Pierre-Clement de Laussat). (LH)
Sponsoring Agency: Department of Education, Washington, DC.
ERIC Note: For the other volumes in this series, see SO 016 725-730. Two chapters are presented in French.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Acculturation; Biculturalism; Colonial History (United States); Cross Cultural Studies; Cultural Education; Cultural Influences; Cultural Pluralism; Culture; Ethnic Groups; Governance; Industrialization; Land Settlement; Slavery; Social History; Social Studies; Subcultures; United States History; War; Franco Americans -- Louisiana; Acadians -- Eighteenth Century -- French Culture -- Louisiana (New Orleans) -- Private Enterprise; Historical Materials; Opinion Papers; Collected Works, General